Psychological and Socio-Economical Determinants of Health: The Case of Inner German Migration - Schmalbach, Bjarne; Schmalbach, Ileana; Kasinger, Christoph; Petrowski, Katja; Brähler, Elmar; Zenger, Markus; Stöbel-Richter, Yve; Richter, Ernst Peter; Berth, Hendrik (Frontiers in Public Health, 2021)
A substantial body of research has shown worse health conditions for East- vs. West-Germany in the wake of reunification. In the present study, we investigate how these differences between the two formerly divided regions developed and what maintains them. Specifically, we consider the associations between health status, income satisfaction, and health-related locus of control. In a quasi-experimental and longitudinal study design, we are particularly interested in the differences between individuals who stayed in East-Germany and those who were born in the East but migrated to West-Germany. To this end, we examined data from seven waves of the Saxony Longitudinal Study (2003–2009). Specifically, we tested a cross-lagged panel model with random effects, which evinced very good model fit. Most parameters and processes were equivalent between individuals who stayed in East-Germany vs. moved to West-Germany. Crucially, there was the expected pattern of positive correlations between health, income, and locus of control. In addition, we found substantially lower values for all three of these variables for the individuals who stayed in East-Germany (vs. moved to West-Germany). A possible explanation is the increase in socio-economic status that the internal migrants experienced. These findings present an important contribution of research in order to foster a better understanding on the social dynamics in Germany related to internal/domestic migrants and implications in the context of health outcomes (e.g., significantly more unemployment in East vs. West-Germany), especially since almost 20–25% of East-German citizens migrated to West-Germany. Until now, there are no similar studies to the Saxony longitudinal project, since the data collection started in 1987 and almost every year an identical panel has been surveyed; which can be particularly useful for health authorities. The study mainly focuses on social science research and deals with the phenomenon of reunification, approaching several subjects such as mental and physical health, quality of life and the evaluation of the political system. Yet even though many people have experienced such a migration process, there has been little research on the subjects we approach. With our research we deepen the understanding of the health consequences of internal migration.